2014
DOI: 10.1038/bjc.2014.283
|View full text |Cite
|
Sign up to set email alerts
|

Statins, 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors, potentiate the anti-angiogenic effects of bevacizumab by suppressing angiopoietin2, BiP, and Hsp90α in human colorectal cancer

Abstract: Background:Statins, 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors, are commonly prescribed because of their therapeutic and preventive effects on cardiovascular diseases. Even though they have been occasionally reported to have antitumour activity, it is unknown whether statins have anti-angiogenic effect in human colorectal cancer (CRC).Methods:A total of 11 human CRC cell lines were used to test the effects of bevacizumab, statins, and bevacizumab plus statins on human umbilical vein endothelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 43 publications
2
44
0
Order By: Relevance
“…56 Previous reports showed that VEGF enhanced the ability of HUVEC to organize into tubular networks on Matrigel 57 and that tube formation is reduced by VEGF inhibitors or siRNA. 58,59 PF0 (100 nmol/l) treatment showed a nonsignificant ( P < 0.05) decrease in tube segments length compared to control ( Figure 6a , e ). Previous studies showed that higher concentrations of PI3K/mTOR dual inhibitors (1 µmol/l) significantly ( P > 0.05) decreased HUVEC tube formation and tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 88%
“…56 Previous reports showed that VEGF enhanced the ability of HUVEC to organize into tubular networks on Matrigel 57 and that tube formation is reduced by VEGF inhibitors or siRNA. 58,59 PF0 (100 nmol/l) treatment showed a nonsignificant ( P < 0.05) decrease in tube segments length compared to control ( Figure 6a , e ). Previous studies showed that higher concentrations of PI3K/mTOR dual inhibitors (1 µmol/l) significantly ( P > 0.05) decreased HUVEC tube formation and tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 88%
“…In previous studies, we demonstrated anticancer properties of simvastatin in GC and CRC both in vitro and in vivo (30)(31)(32)(33)(34). However, its role as a potential ionizing radiation sensitizer or adjunct to radiation has not been investigated in either GC or CRC.…”
Section: Introductionmentioning
confidence: 98%
“…16,17 Beyond lipid-lowering activity, accumulating evidence demonstrates that statins also exhibit anti-inflammatory and anti-tumour activities. 23,24 Epidemiologic studies also showed the concomitant use of statins might be beneficial to cancer outcomes. 14,[20][21][22] In experimental animal models, statins are capable of suppressing angiogenesis, tumour invasion and metastasis.…”
Section: Introductionmentioning
confidence: 99%